Anxiolytic Effects of Repeated Cannabidiol Treatment in Teenagers With Social Anxiety Disorders - Masataka, Nobuo (Frontiers in Psychology, 2019)
Accumulated evidence indicates that cannabidiol (CBD), a nonpsychotomimetic and nonaddictive main component of the Cannabis sativa plant, reverses anxiety-like behavior. The purpose of the present study was to assess the efficacy of CBD treatment for Japanese late teenagers with social anxiety disorder (SAD). Thirty-seven 18–19-year-old Japanese teenagers with SAD and avoidant personality disorder received, in a double-blind study, cannabis oil (n = 17) containing 300 mg CBD or placebo (n = 20) daily for 4 weeks. SAD symptoms were measured at the beginning and end of the treatment period using the Fear of Negative Evaluation Questionnaire and the Liebowitz Social Anxiety Scale. CBD significantly decreased anxiety measured by both scales. The results indicate that CBD could be a useful option to treat social anxiety.